Pembuatan Aplikasi Multiplayer Card Game Berbasis Android - Adrian Wiyanto; Kristo Radon Purba; Ibnu Gunawan (Jurnal Infra, 2015)
There are a lot of card games or card games circulating today and demand a lot of circles, one of which is CardFight Vanguard. But some enthusiasts of this game wants to play but with the price of the card is quite expensive so often they only see or borrow from others.With the use of smartphones are widely used today by children and adults, an application designed to help these card players.This application provide cards that can be used by users of this application to make a deck that will be used to play, by using Wi-Fi technology users can play with other users during both connected to the same network connection.Based on testing, this application can run the DeckEdit function where users can create decks and functions as the original game on the Play menu where the user can play with other users.